Facile synthesis of silver nanoparticles using Averrhoa bilimbi L and Plum extracts and investigation on the synergistic bioactivity using in vitro models - Sagadevan, Suresh; Vennila, Selvaraj; Singh, Preeti; Lett, Jayasingh Anita; Johan, Mohd Rafie; Marlinda, Ab Rahman; Muthiah, Bavanilatha; Lakshmipathy, Muthukrishnan (De Gruyter, 2019)
The bacterial communities (Gram-negative and Gram-positive) form the biofilms which oppose the mode of action of antibiotics and affecting the immune system of the human. These chronic infections related to biofilm are always hard to be cured because of their inherent resistance to both antimicrobial agents and host defense. The present study is devoted to the synthesis of silver nanoparticles (AgNPs) using aqueous extracts of Averrhoa bilimbi leaf and Plum fruit (Prunus bokharensis) and its inhibitory effect on Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa, and Salmonella typhi. Here, AgNPs) were successfully prepared by green synthesis method obtained by the reduction of silver nitrate into silver ions. The synthesized AgNPs were characterized by UV-Vis Spectroscopy, XRD, FTIR, FESEM-EDAX and DLS analysis. The antimicrobial effects of the two extract were evaluated by the disk diffusion method. The green synthesized AgNPs exhibited good antibacterial activity against both Gram-negative and Gram-positive. They were also analyzed for their significant antibacterial activities against all the test cultures exposed whereas Escherichia coli and Salmonella typhi topped among other test cultures. The anti-proliferative activity of phytochemical mediated synthesis of Ag NPs was investigated for their cytotoxicity in Vero and Human epidermoid larynx carcinoma cell lines (HEp-2) based on their viability using MTT assay. The present study also represents the synergistic bioactivity of silver nanoparticles using in vitro models. © 2019 Sagadevan et al., published by De Gruyter.